The Singularity of AI? Toward a new philosophical-theological intelligence - Ullrich, Calvin D. (Stellenbosch Theological Journal, 2024)
This article presents a series of reflections on the so-called ‘singularity’ of Artificial Intelligence (AI). It begins with a meditation on Freud’s notion of the ‘Uncanny’ to help us understand the experience of interacting with the new AI. It then critically engages the formal notion of ‘the singularity’ by returning to the classical critique of artificial computing in Hubert Dreyfus, and suggests that ‘singularity’ should be understood rather in its effects within the context of a socio-cultural phenomenon which progressively disembodies the human being. Finally, in conversation with Dominique Janicaud and Emmanuel Falque, it begins to outline the contours of an alternative ‘philosophical-theological intelligence’: characterized by ambivalence, the ‘potentiality’ of rationality, and the finitude of our human condition that Christ came to fully embody and share with us, not so that we might escape it, but ‘undergo’ it in common together.